Maoism and grassroots religion: the Communist revolution and the reinvention of religious life in China - Wang, Xiaoxuan (Oxford University Press, 2020)
"This book explores grassroots religious life under and after Mao in Rui'an County, Wenzhou of southeast China, a region widely known for its religious vitality. Drawing hitherto unexplored local state archives, records of religious institutions, memoirs and interviews, it tells the story of local communities' encounter with the Communist revolution, and its consequences, especially the competitions and struggles for religious property and ritual space. It demonstrates that, rather than being totally disrupted, religious life under Mao was characterized by remarkable variance and unevenness and was contingent on the interactions of local dynamics with Maoist campaigns-including the land reform, the Great Leap Forward, and the Cultural Revolution. The revolutionary experience strongly determined the trajectories and development patterns of different religions, inter-religious dynamics and state-religion relationships in the post-Mao era. This book argues that Maoism was destructively constructive to Chinese religions. It permanently altered the religious landscape in China, especially by inadvertently promoting the localization and even (in some areas) expansion of Protestant Christianity, as well as the reinvention of traditional communal religion. In this vein, the post-Mao religious revival had deep historical roots in the Mao years, and cannot be explained by contemporary economic motives and cultural logics alone. This book calls for a renewed understanding of Maoism and secularism in the People's Republic of China"--